The Influence of Educational Games Tools on Students’ Cognitive Ability in Geometry of Students Group A - Fitriana, Desy Ayu; Windiarti, Rina (BELIA: Early Childhood Education Papers, 2020)
This research has been done to respond the lower range of students’ cognitive ability in group A to recognize shape of geometry in Al Irsyad kindergarten Pemalang. The main question in this research was is there any influence in using the educational games tools on the cognitive ability in geometry of students in kindergarten A? This research aimed to find out is there any influence of Educational Games Tools (APE) on students ‘ability in recognizing the shape of geometry. The subjects of this research are students in group A in Al-Irsyad kindergarten, Pemalang. This research used quantitative approach with the types of pre-experiment and research design one group pre-post test where the researcher observed before and after the treatment.. The researcher chooses the samples with purposive sampling, there are 30 students. This study find out the average of pre-test score 1,83 lower than the average of post-test score 3,07. Statistic examined with normality test using one sample kolmogorov smirnov test find out the score 0,200 > α = 0,05, with the normal distributional data. From the Paired T-test program SPSS 24.0 version find out the result score Sig as 0,00 < 0,05 and score -thitung <-ttabel (-28,358 < -2,0452). Therefore, Ho refused and Ha accepted. We can conclude that APE influence on the students’ cognitive ability in to recognize students geometry group A.